Root restriction affects leaf growth and stomatal response: the role of xylem sap ABA - Ismail, Mohd Razi; Davies, W.J. (Elsevier, 1998)
The effects of a restricted root zone (RRZ) on leaf and root growth, water relations, stomatal conductance (g(s)) and xylem sap abscisic acid concentration ([ABA]) were studied in pepper (Capsicum annum cv Bellboy) plants. Plants were grown in soil columns of two different volumes (0.5 l (restricted root) and 2.25 l (unrestricted root) control) in a controlled environment growth cabinet. Another group of plants were grown without root restriction but a gradual soil drying treatment was imposed. Root restriction for 19 days reduced leaf and root growth almost to the rate shown by plants exposed to soil drying. Leaf water potential of RRZ plants was similar to that of unrestricted plants, but, g(s) was reduced in plants undergoing root restriction. The slight increase of xylem sap ABA concentration in RRZ plants did not fully account for the large reductions in leaf growth and g(s).